Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
[tex]k=-\dfrac{11}{2}[/tex]
[tex]\left(x+\dfrac{7}{2}\right)[/tex]
Step-by-step explanation:
[tex]\boxed{\begin{minipage}{5.7 cm}\underline{Factor Theorem}\\\\If f$(x)$ is a polynomial, and f$(a) = 0$,\\then $(x-a)$ is a factor of f$(x)$.\end{minipage}}[/tex]
Given polynomial function:
[tex]p(x)=x^2-kx+7[/tex]
Apply the Factor Theorem:
[tex]\begin{aligned} \textsf{If $(x + 2)$ is a factor of $p(x)$ then: \quad}p(-2)&=0\\\\\implies (-2)^2-k(-2)+7&=0\\4+2k+7&=0\\2k+11&=0\\2k&=-11\\k&=-\dfrac{11}{2}\end{aligned}[/tex]
Substitute the found value of k into the original function:
[tex]\implies p(x)=x^2-\left(-\dfrac{11}{2}\right)x+7[/tex]
[tex]\implies p(x)=x^2+\dfrac{11}{2}x+7[/tex]
As (x + 2) is factor of the polynomial, and the leading coefficient of the function is 1, the other factor will be (x + q) where q is a constant to be found.
[tex]\begin{aligned}x^2+\dfrac{11}{2}x+7 & = (x+2)(x+q)\\& = x^2+qx+2x+2q\\& = x^2+(2+q)x+2q \end{aligned}[/tex]
Compare the constant of the given polynomial with the constant of the expanded factors:
[tex]\implies 2q=7[/tex]
[tex]\implies q=\dfrac{7}{2}[/tex]
Therefore:
[tex]\implies x^2+\dfrac{11}{2}x+7 = (x+2)\left(x+\dfrac{7}{2}\right)[/tex]
So the other factor of the given polynomial is:
[tex]\left(x+\dfrac{7}{2}\right)[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.